2008
DOI: 10.1111/j.1462-2920.2007.01559.x
|View full text |Cite
|
Sign up to set email alerts
|

Global impact of Vibrio cholerae interactions with chitin

Abstract: SummaryThe interaction of Vibrio cholerae with chitin exemplifies for microbial ecology a successful bacteriasubstrate interaction with complex and significant influence on the lifestyle of the bacterium. Chitin is one of the most abundant polymers on earth and possibly the most abundant in the aquatic environment, where its association with V. cholerae has provided the microorganism with a number of advantages, including food availability, adaptation to environmental nutrient gradients, tolerance to stress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
205
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(210 citation statements)
references
References 91 publications
1
205
2
2
Order By: Relevance
“…Temporal shifts in zooplankton composition and species dominance may promote the proliferation of groups carrying larger V. parahaemolyticus loads. In contrast to the importance of copepods in the ecology of Vibrio populations in estuarine areas (Colwell, 1996;Pruzzo et al, 2008), the results of the present study suggest only a small significance for copepods in the offshore occurrence of V. parahaemolyticus. This study also revealed that two different groups, Cnidaria and Cladocera, are relatively more influential on V. parahaemolyticus levels.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Temporal shifts in zooplankton composition and species dominance may promote the proliferation of groups carrying larger V. parahaemolyticus loads. In contrast to the importance of copepods in the ecology of Vibrio populations in estuarine areas (Colwell, 1996;Pruzzo et al, 2008), the results of the present study suggest only a small significance for copepods in the offshore occurrence of V. parahaemolyticus. This study also revealed that two different groups, Cnidaria and Cladocera, are relatively more influential on V. parahaemolyticus levels.…”
Section: Discussioncontrasting
confidence: 53%
“…Nevertheless, ocean currents have often been proposed as a vehicle for spread of human Vibrio diseases through dispersal of pathogenic specimens attached to zooplankton (Colwell, 1996;Lipp et al, 2002;Halpern et al, 2008;Pruzzo et al, 2008). In recent years, increasing evidence has related major epidemic outbreaks of V. parahaemolyticus to the incursion of oceanic waters of subtropical origin in coastal areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the Vibrio genomes in our data set were capable of complete chitin hydrolysis, which is consistent with their known ecology. Vibrios can be found in a range of aquatic habitats and have one of the most wellstudied chitinolytic systems of any prokaryote (Keyhani and Roseman, 1999;Xibing Li and Roseman, 2004;Pruzzo et al, 2008). While a high proportion of CHI-positive genotypes (73.75%) were also positive for NAG, we detected potential for CHI production without the potential for NAG production in a few groups within the Firmicutes phylum ( Figure 3).…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, however, all trh-and Kanagawa-positive strains were isolated from sediment samples. Organisms that are able to persist in sediment biofilms will more likely be able to colonize other tissues such as skin or the intestinal tract [73]; thus, the role of sediments in putting forth pathogenic clones could be an interesting aspect for future investigations.…”
Section: Discussionmentioning
confidence: 99%